Avaliação da poluição difusa de esgoto doméstico veiculado à bacia hidrográfica urbana - Chamun, Camille Couto (2008)
This study aimed to quantify the diffuse pollution load of domestic sewage discharged into the urban basin. The quantification of these loads is of great importance in order to evaluate their impact and to devise structural control measures, which makes it essential in the analysis of alternatives for water resource management. The area studied was the Cancela basin, located in the city of Santa Maria, RS, with a population of approximately 18082 inhabitants and a drainage area of 4,95 km2. A significant portion of the watershed does not possess a sewer system and sewage is discharged into the urban drainage network. In order to obtain the pollution load, water samples and water flow measurements were taken during two consecutive days, with four collections each day, as the water quality and water flow vary on an hourly basis, due to sewage discharge. The results showed a deterioration in the water quality with parameters within and below the limits established for Class 4 in the CONAMA 357/05 Resolution. Statistical analysis showed that the behavior of parameters was similar for all sections. In general, values of dissolved oxygen and pH showed little variability, however, values of conductivity, turbidity, solids, BOD, COD, total coliforms and Escherichia coli presented great variability due to the hourly variation in sewage discharge. The pollution load was determined for the following parameters of water quality: solid (total, suspended or dissolved), BOD, COD, and Escherichia coli. For each section, the lowest values occurred during the first sample taken in the morning, increased during the day and showed a tendency to decrease in the afternoon. Domestic sewage discharge was shown to be responsible for 119.8 Kg BOD/day and 1.33E+13 NMP/day of Escherichia Coli in the basin. The contribution per capita calculated for the city of Santa Maria, 32.4 g BOD/inhabitant/day, was inferior to values suggested in the literature (54 g BOD/inhabitant/day and 43.3 g BOD/inhabitant/day; PRÓ- GUAÍBA, 1991).